A United States national reference for foetal growth for Asian American ethnicities. (3rd October 2022) - Dongarwar, Deepa; Ibrahimi, Sahra; Salihu, Hamisu M.
Abstract: The purpose of this study was to calculate 10th, 50th, and 90th percentiles of birth weight for gestational age for the total US population and the Asian-American ethnicities. Using the US Natality data files for the years 1992–2020, estimated growth curves were determined across gestational ages and for each Asian American ethnic group—Chinese, Asian Indians, Japanese, Koreans, Filipino, and Vietnamese. Average weight at the 10th, 50th and 90th foetal growth percentiles by race/ethnicity and sex were calculated. Overall, for the 10th, 50th and 90th percentiles, Asian American average birth weight was 18, 90 and 144 g lower than the national average, respectively. We also found that Asian Indians consistently had the lowest birthweight, while Koreans had the highest birthweight among Asian Americans. Updated racial/ethnic-specific weight percentiles by gestational age can be a useful reference for accurate small and large-for-gestational age classifications among different Asian American sub-populations. Impact statement: What is already known on this subject? Foetal growth is an important determinant of infants' immediate and long-term health outcomes and foetal growth reference curves have been developed to provide average birth weights for each week of gestation and identify growth-restricted as well as excess-weighing foetuses. What the results of this study add? Using the U.S. Natality data files for the years 1992–2020, estimated growth curves were determined across gestational ages and for each Asian American ethnic group—Chinese, Asian Indians, Japanese, Koreans, Filipino, and Vietnamese. Average weight at the 10th, 50th and 90th foetal growth percentiles by race/ethnicity and sex were calculated. What the implications are of these findings for clinical practice and/or further research? Updated racial/ethnic-specific weight percentiles by gestational age can be a useful reference for accurate small and large-for-gestational age classifications among different Asian American sub-groups.